Reactive Nitrogen in Turfgrass Systems: Relations to Soil Physical, Chemical, and Biological Properties. Issue 1 (1st January 2015) - Lu, Caiyan; Bowman, Daniel; Rufty, Thomas; Shi, Wei
Abstract : Turfgrass systems contribute to the loading of reactive N to water and air via runoff, leaching, and gas emission. Yet, a comprehensive approach has never been developed to assess N loss potential from turfgrass systems. We used pools and production of reactive N (inorganic N, extractable organic N, and N2 O) to estimate N loss potential and hypothesized that this potential could be predicated by basic soil properties. A total of 68 soil samples were taken from 17 bermudagrass sites in North Carolina. Basic soil properties were analyzed, including soil C and N, C:N ratio, microbial biomass, moisture, pH, and percent silt/clay/sand. Soil samples varied most widely in texture, followed by soil C and N, microbial biomass, moisture, pH, and C:N ratio. The pools of extractable organic N and inorganic N were comparable, indicating that soluble organic N should be considered as a pathway of N loss from turfgrass. Turfgrass with large pools and production of reactive N was characterized by high soil C and N, microbial biomass, and moisture. Because soil C and N accumulate over time after turfgrass establishment, turfgrass age could be a suitable practical indicator of N loss potential and thus could be used to implement changes in management. Pools and production of reactive N in liquid and gas phases were well correlated, suggesting that if a turfgrass system has a high potential of N loss via leaching and runoff, it may also be of a high potential for N2 O emissions.